PENDUGAAN STOK KARBON PADA POLA TANAM AGROFORESTRI SEDERHANA DAN AGROFORESTRI KOMPLEKS DI KPH BATUTEGI, KABUPATEN TANGGAMUS - Christine Wulandari; Sugeng p Harianto; Destia Novasari (Forestry Study Program University Of Mataram, 2021)
Global warming is a natural phenomenon that is currently taking place. Natural phenomena occur as a result of changing ecosystem balance. This can be minimized by adding vegetation which acts as an absorber of CO2 to convert CO2 into glucose and oxygen through the process of photosynthesis. Each type of vegetation has the potential to absorb different carbon, so this can be circumvented by using the right cropping pattern. Therefore, information about the potential for carbon stored in complex and simple agroforestry cropping patterns in KPH Batutegi is important. The purpose of this study was to analyze carbon stocks in agroforestry cropping patterns and to compare carbon stocks in simple and complex agroforestry cropping patterns in KPH Batutegi. Source of living tree biomass, dead tree biomass, understorey biomass, and litter biomass. The results showed that the carbon stored in complex agroforestry cropping patterns fell into the good category according to the Intergovermental Panel on Climate Change (IPCC). However, the stored carbon in complex agroforestry cropping patterns is greater than the stored carbon in simple agroforestry cropping patterns, namely 765.61 tonC/ha and 356.21 tonC/ha.